Periodic movements of the legs during sleep associated with rises in systemic blood pressure. - Ali, N; Davies, R; Fleetham, J; Stradling, J (1991)
We report the relationship between periodic leg movements during sleep and recurrent rises in systemic blood pressure in a patient with narcolepsy. The mean increase in systolic blood pressure following leg movements was 23%, which is of the same order as the rises seen in patients with obstructive sleep apnea. Following treatment with temazepam, the swings in blood pressure were unchanged despite considerably less electroencephalographic evidence of cortical arousal.